2023
DOI: 10.1007/s10854-023-11252-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency enhancement and chrono-photoelectron generation in dye-sensitized solar cells based on spin-coated TiO2 nanoparticle multilayer photoanodes and a ternary iodide gel polymer electrolyte

T. M. W. J. Bandara,
S. M. S. Gunathilake,
G. B. M. M. M. Nishshanke
et al.

Abstract: The effect of the thickness of a multilayer TiO2 photoanode on the performance of a dye-sensitized solar cell (DSC) made with a polyethylene oxide-based gel polymer electrolyte containing ternary iodides and performance enhancer 4-tert-butylpyridine is studied. Multilayer photoanodes consisting of up to seven layers of TiO2 nano-particles (13 nm and 21 nm) are prepared by spin coating of successive layers. XRD results confirm the predominant presence of the anatase phase of TiO2 in the multilayer structure aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Another study explores the efficiency enhancement and chrono-photoelectron generation in dye-sensitized solar cells using spin-coated TiO2 nanoparticle multilayer photoanodes and a ternary iodide gel polymer electrolyte. 126 The study examines the impact of the thickness of a multilayer TiO2 photoanode on the performance of a dye-sensitized solar cell (DSC) using a polyethylene oxide-based gel polymer electrolyte and 4-tertbutylpyridine. The study found that the thickness of TiO2 layers increased photocurrent density and efficiency, with the most efficient cell having a rate of effective photoelectron generation of 1.34 molecule−1 -s−1 and an average time gap of 0.74 s a study focuses on optimizing the microstructure and properties of titanium dioxide for efficient solar cell production.…”
Section: Applications Of Nanosensors In Different Types Of Solar Cellsmentioning
confidence: 99%
“…Another study explores the efficiency enhancement and chrono-photoelectron generation in dye-sensitized solar cells using spin-coated TiO2 nanoparticle multilayer photoanodes and a ternary iodide gel polymer electrolyte. 126 The study examines the impact of the thickness of a multilayer TiO2 photoanode on the performance of a dye-sensitized solar cell (DSC) using a polyethylene oxide-based gel polymer electrolyte and 4-tertbutylpyridine. The study found that the thickness of TiO2 layers increased photocurrent density and efficiency, with the most efficient cell having a rate of effective photoelectron generation of 1.34 molecule−1 -s−1 and an average time gap of 0.74 s a study focuses on optimizing the microstructure and properties of titanium dioxide for efficient solar cell production.…”
Section: Applications Of Nanosensors In Different Types Of Solar Cellsmentioning
confidence: 99%